Investigating dosage effects of ovulation inhibitors on oocyte maturation in assisted reproductive technology: A retrospective study among patients with normal ovarian reserve - Mika Handa; Tsuyoshi Takiuchi; Sumika Kawaguchi; Yasuhiro Ohara; Masakazu Doshida; Takumi Takeuchi; Hidehiko Matsubayashi; Tomomoto Ishikawa; Sho Komukai; Tetsuhisa Kitamura; Tadashi Kimura (PLoS ONE, 2025)
The judicious selection of ovulation inhibitors in ovarian stimulation protocols is crucial for the success of assisted reproductive technology (ART). Herein, we investigate the dose-dependent effects of chlormadinone acetate (CMA) and cetrorelix, two distinct ovulation inhibitors, on oocyte maturation in patients with normal ovarian reserve, using univariable and multivariable Poisson regression analyses. Patients undergoing progestin-primed ovarian stimulation (PPOS) with CMA (n = 299) or gonadotropin-releasing hormone antagonist (GnRH-ant) with cetrorelix (n = 605) during their initial in vitro fertilization cycle were enrolled at our center from March 2018 to October 2020 (N = 904). The primary and secondary outcomes were the oocyte maturation and fertilization rates, respectively. After adjusting for several covariates including age, anti-Müllerian hormone levels, total gonadotropin dose, and type of trigger, we calculated the dose-dependent adjusted relative risk (aRR) and 95% confidence interval (CI) for 1 mg of CMA or 0.25 mg of cetrorelix. In the PPOS group, the median age was 34.0 years, and the median total CMA dosage was 22 mg (interquartile range [IQR]: 18.0–32.0). In the GnRH-ant group, the median age was 35.0 years, and the median total cetrorelix dosage was 0.5 mg (IQR 0.5–0.5). The aRR of the maturation rate was 1.003 (95% CI: 0.999–1.007) with PPOS (p = 0.194) and 1.009 (95% CI: 0.962–1.059) with GnRH-ant (p = 0.717). The aRR of the fertilization rate was 1.002 (95% CI: 0.985–1.020) with PPOS (p = 0.783) and 1.022 (95% CI: 0.839–1.246) with GnRH-ant (p = 0.829). Collectively, these findings indicate that within the applied dosages, ovulation inhibitors do not significantly impact oocyte maturation or fertilization rates in patients with normal ovarian reserve. These valuable insights can be applied when designing ART protocols and may guide clinicians in optimizing infertility treatments.